2021
DOI: 10.1093/rheumatology/keab927
|View full text |Cite
|
Sign up to set email alerts
|

A novel semi-automated classifier of hip osteoarthritis on DXA images shows expected relationships with clinical outcomes in UK Biobank

Abstract: Objective Conventional scoring methods for radiographic hip osteoarthritis (rHOA) are subjective and show inconsistent relationships with clinical outcomes. To provide a more objective rHOA scoring method, we aimed to develop a semi-automated classifier based on dual-energy X-ray absorptiometry (DXA) images, and confirm its relationships with clinical outcomes. Methods Hip DXAs in UK Biobank (UKB) were marked up for osteophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…(14) Moreover, we found that rHOA grade ≥1 to 4 is associated with progressively stronger relationships between rHOA and hospital-diagnosed HOA/subsequent THR. (17) This study has several strengths. We investigated relationships of hip shape with different definitions of HOA in a very large study population.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(14) Moreover, we found that rHOA grade ≥1 to 4 is associated with progressively stronger relationships between rHOA and hospital-diagnosed HOA/subsequent THR. (17) This study has several strengths. We investigated relationships of hip shape with different definitions of HOA in a very large study population.…”
Section: Discussionmentioning
confidence: 98%
“…( 14 ) Moreover, we found that rHOA grade ≥1 to 4 is associated with progressively stronger relationships between rHOA and hospital‐diagnosed HOA/subsequent THR. ( 17 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included UKB participants with a left hip dual-energy X-ray absorptiometry (DXA) scan (iDXA GE-Lunar, Madison, WI). Outline points were automatically placed around each hip and features of radiographic HOA (rHOA) were measured semi automatically as previously described (15, 17, 18). AA was estimated using the outline points that excluded osteophytes (Figure 1) and a previously published Python code (19, 20).…”
Section: Methodsmentioning
confidence: 99%
“…Outcome measures of osteoarthritis and observational associations in UK Biobank UKB participants were asked whether they had hip pain for >3months via questionnaire on the same day as their DXA scan. Hospital diagnosed HOA was based on hospital episode statistics (HES) data, termed HES OA, as was total hip replacement (THR) (17). Logistic regression was used to examine associations between AA with clinical outcomes, apart from with THR which was examined using Cox proportional hazard modelling.…”
Section: Alpha Anglementioning
confidence: 99%